RADICAL AND LIBERAL FEMINISM IN ALICE WALKER’S THE COLOR PURPLE: AN INTERSECTIONAL AND SOCIOLOGICAL INQUIRY - Hasibuan, Derliana; Barus, Efendi; Siwi, Purwanto; Nuzwaty, Nuzwaty (Universitas Islam Sumatera Utara, 2025)
This study explores feminist themes in Alice Walker’s The Color Purple, with a particular focus on the character of Celie as a symbol of resistance and empowerment. It aims to identify and analyze various forms of feminism represented in the novel, emphasizing how Celie challenges traditional gender roles and societal expectations. Employing a sociological approach to literature and drawing on feminist theories—specifically liberal and radical feminism—the research traces Celie’s transformative journey toward self-liberation. The findings reveal that Celie embodies both liberal and radical feminist ideals through her rejection of patriarchal authority and her pursuit of personal autonomy and gender equality. Her evolution—from a silenced and oppressed figure to a self-reliant provider and assertive individual—demonstrates themes of self-determination and resistance to gender norms. Celie’s portrayal as a resilient and resourceful woman, often exhibiting traits culturally coded as masculine, serves to critique gender stereotypes and advocate for a broader understanding of strength and leadership. Ultimately, The Color Purple stands as a powerful narrative that interrogates gender boundaries, promotes feminist discourse, and underscores the potential of individual agency to inspire social change. This qualitative study analyzes the original English version of the novel as its primary data source, with data—comprising words, dialogues, and key passages—collected through close reading and systematic note-taking. The analysis, grounded in the sociology of literature, identifies and interprets feminist elements to achieve the study’s objectives.